Gene delivery of neurturin to putamen and substantia nigra in Parkinson disease: A double‐blind, randomized, controlled trial. Issue 2 (10th June 2015) - Warren Olanow, C.; Bartus, Raymond T.; Baumann, Tiffany L.; Factor, Stewart; Boulis, Nicholas; Stacy, Mark; Turner, Dennis A.; Marks, William; Larson, Paul; Starr, Phillip A.; Jankovic, Joseph; Simpson, Richard; et al.
<x xml:space="preserve">Abstract</x> Objective A 12‐month double‐blind sham‐surgery–controlled trial assessing adeno‐associated virus type 2 (AAV2)‐neurturin injected into the putamen bilaterally failed to meet its primary endpoint, but showed positive results for the primary endpoint in the subgroup of subjects followed for 18 months and for several secondary endpoints. Analysis of postmortem tissue suggested impaired axonal transport of neurturin from putamen to substantia nigra. In the present study, we tested the safety and efficacy of AAV2‐neurturin delivered to putamen and substantia nigra. Methods We performed a 15‐ to 24‐month, multicenter, double‐blind trial in patients with advanced Parkinson disease (PD) who were randomly assigned to receive bilateral AAV2‐neurturin injected bilaterally into the substantia nigra (2.0 × 1011 vector genomes) and putamen (1.0 × 1012 vector genomes) or sham surgery. The primary endpoint was change from baseline to final visit performed at the time the last enrolled subject completed the 15‐month evaluation in the motor subscore of the Unified Parkinson's Disease Rating Scale in the practically defined off state. Results Fifty‐one patients were enrolled in the trial. There was no significant difference between groups in the primary endpoint (change from baseline: AAV2‐neurturin, −7.0 ± 9.92; sham, −5.2 ± 10.01; p = 0.515) or in most secondary endpoints. Two subjects had cerebral hemorrhages with transient symptoms. No clinically meaningful adverse events were attributed to AAV2‐neurturin. Interpretation AAV2‐neurturin delivery to the putamen and substantia nigra bilaterally in PD was not superior to sham surgery. The procedure was well tolerated, and there were no clinically significant adverse events related to AAV2‐neurturin. Ann Neurol 2015;78:248–257